Human immune responses to schistosoma japonicum recombinant and native antigens - Acosta, Luz Pablo (1999)
Cellular and humoral responses to specific S. japonicum recombinant and native antigen investigated in a well-defined study population of 155 individuals who belonged to a previous intensive water contact study in Jaro, Leyte. Population exposure and reinfection patterns were described based on available data from a e-year study of water contact observation and yearly reinfection after treatment. In this study, an attempt was made to categorically identify putative ?resistant? individuals whose relative lack of reinfection after yearly treatment could not be attributed to a lack of exposure. Peripheral blood mononuclear cell proliferation, cytokine (IFN-u, IL-5 and IL-10) production and antibody isotypic responses to defined recombinant and native antigens were measured. The antigens that were tested include the following recombinant antigens: 97 kDa full-length paramyosin (rPMY), 22 kDa tegumental antigen (rTEG), 14 kDa fatty-acid binding protein (rFABP); a 37 kDa glyceraldehyde-3-phosphate dehydrogenase (Rrapdh) and 28 kDa gluthathione-S-transferase (Rgst28). Immune responses to native soluble worm extracts (SWAP) and egg antigens (SEA) were also measured. Specific immune responses to these antigens were tested for possible relationships with several epidemiological parameters such as age, sex, exposure and infection intensity. Particular antigen-specific immune response among ?resistant? or ?susceptible? individuals were also assessed with the aim to associate and describe the immune response that these individuals have toward the antigens.